2014
DOI: 10.12968/bjon.2014.23.22.1174
|View full text |Cite
|
Sign up to set email alerts
|

A proven pathway for stoma care: the value of stoma care services

Abstract: The role of the stoma nurse is often misunderstood by those who have little or no understanding of the complexities of their role. Stoma nurses face challenges when communicating the valuable role they provide in relation to quality, value and cost. The implementation of an accredited pathway designed specifically for stoma patients would not only promote excellence in nursing practice, but would also assist the stoma nurse in building the profile of the specialty. The accredited pathway should outline the seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 11 publications
0
8
0
5
Order By: Relevance
“…with a new stoma but also cut costs to the health service through reducing readmissions, GP visits, and outpatient appointments and through a decreased waste of products (Davenport, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…with a new stoma but also cut costs to the health service through reducing readmissions, GP visits, and outpatient appointments and through a decreased waste of products (Davenport, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Porrett (2005) recommended that people are seen at home within the first 48 hours to a week after discharge home to assess how well they are dealing with their new stoma and to act promptly on any potential problems. It has also been suggested that routine home visits, rather than a problem-focused approach, can prevent significant stoma-related morbidity by identifying problems ostomates do not realise they have (Johnson, 2012), Davenport (2014) expanded on this, suggesting the use of a structured home support system, which would be enhanced if patients were reviewed again at 3 and 6 months after surgery. This home support has been shown to not only benefit people study; at present, there are no national guidelines on outpatient follow up of people with a stoma.…”
Section: Discussionmentioning
confidence: 99%
“…Nurses play an important role to maintain patients' ability in performing self-care 12 , including adjusting with their colostomy. The transition from hospital to home after colostomy surgery can be difficult for the patient 13 as it takes time to adjust to the colostomy.…”
Section: Introductionmentioning
confidence: 99%
“…Various educational intervention models that can be provided by ET nurses include education to improve psychosocial skills and self-management 16 , group discussion on colostomy self-care curriculum using a chronic care model to improve Health Related Quality of Life (HRQOL) and self-management 17 , experience-sharing group education programs including stoma care and social activities to improve QoL 18 , and structured education to improve QoL and reduce costs 19 . Thus, the vital role of the interaction between the ET nurses and structured follow-up in the first year after a colostomy is to improve QoL and reduce the severity of peristomal skin conditions (PSCs) and the cost of care 13 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation